Peran komunikasi interpersonal ibu untuk membangun percaya diri anak dalam perspektif orang tua - Rahmahnda, Nur Anisah (Komunika: Journal of Communication Science and Islamic Dakwah, 2022)
Interpersonal communication is communication performed by two people. In this research interpersonal communication is focused on mother and child. A mother's and child's interpersonal communication can have a special effect on the child's confidence. The role of the mother in communication with the child comes first than the father, because a mother has more to do with it since a child is born and is always by her side. Thus the author hopes through this study that parents will be able to provide the best education for the child especially in establishing interpersonal communication. Moreover, because the first education is vital and has a bearing on a child's future behavior or behavior, especially to build a strong and brilliant generation of confidence in the child. The purpose of this study is to know that the importance of communicating with children is because if it does not occur to the mother with the child, they will not have confidence. These research methods employ qualitative methods by jumping into the field and interviews and observation. It has been found that interpersonal communication with children can affect a child's confidence because it is important for the mother to be the first school for children, especially in her neighborhood as at home. Mothers must be able to communicate with their children often, such as by studying, reading, playing with them, and telling stories with them. The more mothers communicate with their children, the more confident the child will be. Abstract Komunikasi interpersonal adalah komunikasi yang dilakukan oleh dua orang. Pada penelitian ini komunikasi interpersonal berfokuskan kepada ibu dan anak. Adanya komunikasi interpersonal ibu dan anak dapat berpengaruh khususnya kepada salah satu karakter sang anak, yaitu percaya diri. Peran ibu dalam komunikasi dengan anak lebih diutamakan daripada dengan peran ayah sebab ibu mempunyai peran lebih banyak sejak seorang anak itu lahir dan selalu ada disampingnya. Selain itu, lantaran pendidikan pertama sangatlah penting dan berpengaruh untuk perilaku atau tingkah laku anak pada masa depan, khususnya untuk membangun kepercayaan diri anak menjadi generasi yang kuat dan cemerlang. Metode penelitian ini menggunakan metode kualitatif dengan cara terjun langsung ke lapangan, wawancara, dan observasi. Dari hasil temuan didapatkan bahwa komunikasi interpersonal ibu dengan anak dapat berpengaruh terhadap rasa percaya diri anak sebab pentingnya ibu sebagai sekolah pertama bagi anak khususnya di lingkungannya sehari-hari seperti di rumah. Ibu harus bisa sering berkomunikasi dengan anak seperti belajar, membaca, menemani anak bermain, serta bercerita dengan anak. Semakin ibu sering berkomunikasi dengan anak maka anak akan mempunyai rasa percaya diri. Dengan dibuatnya jurnal ini penulis berharap melalui penelitian ini orang tua mampu memberikan pendidikan yang terbaik bagi anak terutama dalam membangun komunikasi interpersonal.